2010
DOI: 10.1007/s11999-009-1179-x
|View full text |Cite
|
Sign up to set email alerts
|

Weight of Polyethylene Wear Particles is Similar in TKAs with Oxidized Zirconium and Cobalt-chrome Prostheses

Abstract: Background The greater lubricity and resistance to scratching of oxidized zirconium femoral components are expected to result in less polyethylene wear than cobaltchrome femoral components. Questions/purposes We examined polyethylene wear particles in synovial fluid and compared the weight, size (equivalent circle diameter), and shape (aspect ratio) of polyethylene wear particles in knees with an oxidized zirconium femoral component with those in knees with a cobalt-chrome femoral component. Patients and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…30 Kim et al compared synovial fluid with respect to PE particle amount, size, and shape in 100 patients with OxZr implants in one knee and CoCr implants in the contralateral knee finding no significant differences. 31 In summary, the clinical results comprising prospective cohort studies, prospective randomized controlled studies, and registry data showed no significant differences in patients with conventional CoCr implants and OxZr implants. Analyses of synovial fluids showed no differences either.…”
Section: Clinical Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…30 Kim et al compared synovial fluid with respect to PE particle amount, size, and shape in 100 patients with OxZr implants in one knee and CoCr implants in the contralateral knee finding no significant differences. 31 In summary, the clinical results comprising prospective cohort studies, prospective randomized controlled studies, and registry data showed no significant differences in patients with conventional CoCr implants and OxZr implants. Analyses of synovial fluids showed no differences either.…”
Section: Clinical Resultsmentioning
confidence: 86%
“…The authors concluded, that longer follow-up periods are necessary than the investigated 7 years to show a potential benefit of "premium TKAs." 29 Clinical data including results from synovial fluid aspirations were reported by Minoda et al 30 and Kim et al 31 Minoda et al evaluated the amount and size of PE particles in the synovial fluid from six patients with OxZr TKAs and from six patients with CoCr TKAs finding no significant differences in both groups. 30 Kim et al compared synovial fluid with respect to PE particle amount, size, and shape in 100 patients with OxZr implants in one knee and CoCr implants in the contralateral knee finding no significant differences.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Reports of high-flexion knees [2,23,27], mobile-bearing knees [6,24], oxidized-zirconium femoral components [22,35], and moderately crosslinked polyethylene inserts [29,31,32] have not been consistently associated with either improved function or survival when compared to standard lower-cost designs. All-polyethylene tibial components have demonstrated similar or better mid-to long-term results than metalbacked tibial component designs at lower cost [1,11,12,33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrieval study revealed less surface damage on UHMWPE components that articulated against OxZr than components paired with CoCr [12]. Several series have compared OxZr TKA components with conventional bearing surfaces [14,17,18]; however, superiority of OxZr has not been demonstrated in terms of better implant survival, at least at midterm followup.…”
Section: Introductionmentioning
confidence: 99%